DUNIA BENTUKAN ORANG TUA : Kajian Fenomenologi tentang Isolasi Sosial Terhadap Anak dan Pembentukan Konsep Diri Serta Karakter Anak - Pandan Yudhapramesti (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2016)
To prevent unwanted social danger of the association of children outside the home, some parents build a specific strategy in raising children, to raise children in a social environment that is controlled parent.To limit the social pollution, parents in this category strictly limiting social affiliation or participation of children in social environments outside the home, or create social isolation of children while the formation of self-concept and character progress. This study uses a phenomenological approach, explore the everyday experience of informants about the concept of social isolation that they do to the child, during the formation of character and self-concept of children, or as it is called Berger and Luckmann during primary socialization. The results showed that the primary socialization period is a crucial moment in the formation of self-concept and character of a child. During this period, the social isolation and protection of the parents needs to be done so that the child can absorb the meanings and values espoused parents, without much intervention from other people. After the meanings and values of parents are fully internalized in the child, then the children are introduced to the wider social environment outside the protection of the parents. Social isolation and protection of the parents will be removed when the child has been able to take decisions in accordance with the values expected of parents and able to protect himself. This belief is making your child through primary socialization period longer than the other children, but the parents who developed this concept believe this strategy will create the self concept and character of the child becomes stronger against the influence of social pollution.